STRATEGI PEMASARAN PADA TOKO BERAS RH DALAM RANGKA MENINGKATKAN PENJUALAN DI MASA PANDEMI COVID 19 - Rizky Natassia; Hayu Yolanda Utami (XXXXX, 2022)
Staple food is one of the primary needs of society that is difficult to ignore under any conditions, including the economic crisis. This makes the basic commodities trading business one of the crisis-resistant business sectors. With conditions like this, it will trigger the emergence of similar businesses so that it is likely that this business will mushroom. Therefore, it is necessary to have special abilities from business actors to be able to compete so that they can increase their sales. The purpose of this service is to increase the partner's ability to understand how to implement an effective and efficient marketing strategy. The method used in the implementation of service is in the form of counseling. The results obtained from the implementation of this service are the increased ability of partners in implementing marketing strategies that can be used to win competition in the market.